Strategi Personal Branding Musisi Pop Jawa Melalui Media Sosial - Dadang Dwi Septiyan (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2021)
Advances in information technology and social media are now increasing. This makes it easier for anyone to form a personal brand through social media. Having an attractive identity is a must for a musician, whether it's self-identity or work identity. The purpose of this study is to find out and understand the personal branding strategy of musicians through social media. This study uses qualitative methods with data collection techniques, namely interviews and observing the documentation they have and conducting a literature review. The data obtained were then analyzed using analytical techniques, namely sorting out data, reducing data, summarizing, and presenting data. The findings of this study are that the personal branding strategy of musicians through social media, especially Instagram, uses indicators consisting of 7 classifications borrowed from Mateusz Grzesiak's concept. The results of the study stated that the personal branding strategy carried out by several samples of musicians had values, characters, goals, methods, dialectics, visualizations, media, awareness levels, challenges, cultural models, and strategies each through Instagram media and in their daily lives.